The glaciers of Mount Kenya 1899-2004 - Hastenrath, Stefan (ERDKUNDE, 2005)
A map is presented documenting the century-long history of glacier recession on Mount Kenya. Observations from early expeditions provide evidence from the end of the 19th century to the 1940's, and photogrammetric mappings in 1947, 1963, 1974, 1978, 1982, 1985, 1986, 1987, 1993 and 2004, give quantitative detail for the later decades. Of the eighteen ice entities at the end of the 19th century, one glacier may have disappeared before 1926, five vanished after 1926, one after 1978, and one after 1993. All other glaciers also suffered substantial shrinkage, especially from the 1970's onward. Mount Kenya, right under the Equator, is the mountain with best documentation of glacier recession in all of the tropics.